Prevalence of somatic mutl homolog 1 promoter hypermethylation in Lynch syndrome colorectal cancer. Issue 9 (29th December 2014) - Moreira, Leticia; Muñoz, Jenifer; Cuatrecasas, Míriam; Quintanilla, Isabel; Leoz, Maria Liz; Carballal, Sabela; Ocaña, Teresa; López‐Cerón, María; Pellise, Maria; Castellví‐Bel, Sergi; Jover, Rodrigo; Andreu, Montserrat; et al.
<x xml:space="preserve">Abstract</x> BACKGROUND Colorectal cancers (CRCs) that have microsatellite instability (MSI) and mutL homolog 1 (MLH1) immunoloss are observed in 3 clinical scenarios: Lynch syndrome (LS), sporadic MSI CRC, and Lynch‐like syndrome (LLS). v‐Raf murine sarcoma viral oncogene homolog B1 (BRAF) mutational analysis is used to differentiate LS from sporadic MSI CRC. The role of MLH1 promoter methylation status for the differential diagnosis of these clinical forms is not well established. The objectives of this study were: 1) to analyze MLH1 promoter methylation in MLH1‐deficient CRCs by pyrosequencing, and 2) to assess its role in the differential diagnosis of MLH1‐deficient CRCs. METHODS In total, 165 CRCs were analyzed, including LS (n = 19), MSI BRAF‐mutated CRC (n = 37), MSI BRAF wild‐type CRC (n = 60), and a control group of CRCs without MSI (microsatellite stable [MSS] CRC; n = 49). MLH1 promoter methylation status was analyzed by pyrosequencing, and the ability of different strategies to identify LS was assessed. RESULTS The average ± standard deviation methylation in LS (9% ± 7%) was significantly lower than that in MSI BRAF‐mutated CRC (42% ± 17%; P < .001) and in MSI BRAF wild‐type CRC (25% ± 19%; P = .002). Somatic MLH1 hypermethylation was detected in 3 patients (15.8%) with LS, in 34 patients (91.9%) with MSI BRAF‐mutated CRC, and in 37 patients (61.7%) with MSI BRAF wild‐type tumors. Patients with MSI BRAF wild‐type, unmethylated tumors (ie, LLS) had a stronger family history of CRC than those who had tumors with MLH1 methylation (P < .05). The sensitivity for ruling out LS was 100% for BRAF analysis, 84.2% for MLH1 methylation analysis, and 84.2% for the combination of both analyses. CONCLUSIONS Somatic MLH1 promoter methylation occurs in up to 15% of LS CRCs. Somatic BRAF analysis is the most sensitive strategy for ruling out LS. Patients who have CRCs with loss of MLH1 protein expression and neither BRAF mutation nor MLH1 methylation resemble patients with LS. Cancer 2015;121:1395–1404. © 2014 American Cancer Society.